Human papilloma virus vaccination: practical guidelines - Yadav, Kiran; Yadav, Kaushal; Gupta, Sabhyata (International Journal of Research in Medical Sciences, 2017)
Cervical cancer has a long latency period and established role of HPV lead to interest in development of HPV vaccine. Main goal of HPV vaccination is to decrease cervical cancer incidence. There are two vaccines available, for the prevention of HPV infection - gardasil and cervarix. Gardasil is quadrivalent and cervarix is bivalent. The FDA has approved gardasil in 2006 and cervarix in 2009 based on their efficacy in phase 3 trails. When recommending HPV immunization of females, it should be offered to girls 11 to 12 years of age, but can be administered as early as nine years. Catch-up vaccination should be offered for females aged 13 to 26 years who have not been previously vaccinated. HPV immunization is not effective in clearing cytological evident disease or HPV infection that is already present and it does not provide immunization for serotypes other than included in vaccine. Cervical cancer screening is recommended to continue as per guidelines.